The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0134216
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Helicobacter pylori Infection in Nepal: Specific Ancestor Root

Abstract: Prevalence of Helicobacter pylori infection in Nepal, a low-risk country for gastric cancer, is debatable. To our knowledge, no studies have examined H. pylori virulence factors in Nepal. We determined the prevalence of H. pylori infection by using three different tests, and the genotypes of virulence factors were determined by PCR followed by sequencing. Multilocus sequence typing was used to analyze the population structure of the Nepalese strains. The prevalence of H. pylori infection in dyspeptic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 43 publications
5
33
1
3
Order By: Relevance
“…Although it was varied between studies (16.3–70.5 %) [1419], we confirmed the prevalence of H. pylori infection is 38.4 % (56/146) using several diagnostic test that significantly related to source of drinking water [20]. The majority of strains are so-called Western-type- cagA in Nepal as similar to typical South Asian patterns [20].…”
Section: Introductionsupporting
confidence: 75%
“…Although it was varied between studies (16.3–70.5 %) [1419], we confirmed the prevalence of H. pylori infection is 38.4 % (56/146) using several diagnostic test that significantly related to source of drinking water [20]. The majority of strains are so-called Western-type- cagA in Nepal as similar to typical South Asian patterns [20].…”
Section: Introductionsupporting
confidence: 75%
“…Para el análisis comparativo fueron seleccionados 36 estudios, de los cuales 11 (30,55%) relacionan aspectos de ancestría y diversidad genética huésped-hospedero con el desarrollo de lesiones gástricas (9,16,(18)(19)(20)(21)(22)(23)(24)(25) (tabla 3); 10 (27,77%) reportan mecanismos de adaptación de la bacteria (5,11,14,(26)(27)(28)(29)(30)(31)(32)(33) La infección por H. pylori generalmente se adquiere durante la infancia por vía oral o fecal-oral a través del agua, los alimentos y las heces; en las familias, la transmisión requiere contacto íntimo. La presencia de H. pylori varía significativamente entre regiones.…”
Section: Resultsunclassified
“…Es posible que hspAmerindia tienda a desaparecer, dado que carecen de la diversidad necesaria para sobrevivir y competir con las cepas más diversas, traídas por anfitriones no amerindios Kersulyte et al, 2010 (21) Diagnóstico hspAmerindia, presente en los habitantes del pueblo Shimaa, desciende de los asiáticos que llegaron a América hace unos 15 000 años y ha sido desplazada de forma sustancial por hpEuropa en las comunidades menos aisladas del Perú Latifi-Navid et al, 2010 (16) Diagnóstico Las relaciones biogeográficas de H. pylori son probablemente el resultado de la transmisión intrafamiliar combinada con el reciclaje dentro de las comunidades locales. Varios factores de virulencia de H. pylori, que incluyen cagA y vacA, varían su frecuencia según el grupo étnico Martínez et al, 2013 (22) Diagnóstico Las cepas cagA+ y vacA s1/m1 generan lesiones gástricas con un grado de severidad significativamente mayor en las zonas de alto riesgo de CG en comparación con las de riesgo bajo en Colombia Miftahussurur et al, 2015 (23) Diagnóstico hpEuropa genera una inflamación gástrica mayor en la población de Nepal que hpAsia2. La diferencia en la infección entre los países no es suficiente para explicar la diferencia en la incidencia de CG a nivel mundial Shiota et al, 2014 (9) Diagnóstico hpEuropa se asocia significativamente con la gravedad de las lesiones gástricas, pero es insuficiente para distinguir entre el riesgo de CG y úlcera duodenal en la región andina de Colombia.…”
Section: Origen Y Edad De Asociaciónunclassified
See 1 more Smart Citation
“…2,3 H pylorican causes some clinical manifestation such as chronic gastritis, peptic ulcer disease and gastric malignancies. 4,5 The infection induces infiltration of polymorphonuclear that if nor cleared effectively, than replaced gradually by an immunologically-mediated, chronic, and latter induce pro-inflammatory cytokines production by local or systemic, 1,2-6 as aresult, gastric epthelium is not the only one target of H pylori pathologic manifestationbut also affected to some extradigestive conditions, including endocrine disorders, including autoimmune thyroid disorders (ATD) such as autoimmune atrophic thyroiditis and Hashimoto's thyroiditis, or thyroid mucosal associated lymphocyte tissue (MALT) lymphoma that has been epidemiologically proven,. 1,7,8 Even there have been controversial report about the link between H pylori infection and thyroid disorders, but some studies have been sucsesfully reported an increased prevalence of H pylori in people with ATD and relationship between H pylori infection and the presence of high titers of thyroid auto-antibodies, such as antithyroglobulin (anti-Tg) and anti-thyroperoxidase (anti-TPO) antibodies resulting in abnormalities of gastric secrtory fuction.…”
Section: Introductionmentioning
confidence: 99%